Combined LCA and Green Metrics Approach for the Sustainability Assessment of an Organic Dye Synthesis on Lab Scale - Parisi, Maria Laura; Dessì, Alessio; Zani, Lorenzo; Maranghi, Simone; Mohammadpourasl, Sanaz; Calamante, Massimo; Mordini, Alessandro; Basosi, Riccardo; Reginato, Gianna; Sinicropi, Adalgisa (Frontiers in Chemistry, 2020)
New generation photovoltaic devices have attracted much attention in the last decades since they can be efficiently manufactured employing abundant raw materials and with less-energy intensive processes. In this context, the use of powerful environmental assessment is pivotal to support the fine-tuning of solar cells fabrication and hit the target of manufacturing effective sustainable technological devices. In this work, a mass-based green metrics and life cycle assessment combined approach is applied to analyze the environmental performances of an innovative synthetic protocol for the preparation of organic dye TTZ5, which has been successfully proposed as a sensitizer for manufacturing dye sensitized solar cells. The new synthetic strategy, which is based on the C-H activation process, has been compared with the previously reported synthesis employing classic Suzuki-Miyaura cross-coupling chemistry. Results highlight the contribution of direct energy consumption and purification operations in organic syntheses at lab scale. Furthermore, they demonstrate the usefulness of the environmental multifaceted analytic tool and the power of life cycle assessment to overcome the intrinsic less comprehensive nature of green metrics for the evaluation of organic synthesis protocols.